An in-depth evaluation of personal barriers to technology adoption in irrigated agriculture in South Africa. (September 2021) - de Witt, Marlene; de Clercq, Willem Petrus; Velazquez, Francisco José Blanco; Altobelli, Filiberto; Marta, Anna Dalla
Increasing pressure on water resources is driving the development of technology to improve water-use efficiency in irrigation. Uptake of these technological advances are essential to ensure long-term water security in catchments, particularly in water-scarce regions and where agricultural activities and urban centres compete for the same resources. Research suggests that uptake of technology lags far behind the development of new products. The study presented in this paper interviewed 29 commercial farmers from the water-scarce Central Breede River Valley in South Africa to investigate their reasons behind the use or non-use of irrigation technology for scheduling, and in particular the uptake of a free, government-funded remote-sensing service called FruitLook. Evaluating the uptake of a free service eliminates monetary cost as one key barrier to uptake. In-depth interviews revealed a high uptake of technology (83%), but use of only one type – soil water measurement. Among the farmers that use water-use efficiency technology, 78% use the same probe service provider. Perceived accuracy and ease of use, as well as personalised after-sales service are the key reasons for this probe's popularity. While 86% of the farmers have heard about FruitLook, only one farmer uses it for irrigation purposes. The non-use of the free service can mainly be attributed to the time cost associated with the product's initial set-up, use, and interpretation of information. The study revealed that the integration of information from various products is essential for farmers – too much information in different formats is too time-costly. Developers of new technology should focus on these latter two findings to improve the likelihood of new product uptake.